2010
DOI: 10.1007/s11104-010-0659-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Neotyphodium endophyte-tall fescue symbiosis on mineralogical changes in clay-sized phlogopite and muscovite

Abstract: Numerous studies have been conducted to determine the positive effects of Neotyphodium endophye-tall fescue symbiosis on plant resistance to different stresses. However, its effects on the uptake of potassium (K) and transformation of K-bearing minerals are not yet known. The objective of this research was to investigate the possible effects of such symbiosis on the transformation of clay-sized micaceous minerals. Tall fescue genotype 75B, both infected and non-infected with natural Neotyphodium endophyte, was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 49 publications
1
2
0
Order By: Relevance
“…Epichloë endophyte‐infected plants have higher SOC in the rhizosphere than endophyte‐free plants in a 15‐year trial (Franzluebbers et al, 1999). In the present study, we demonstrated that litter containing Epichloë endophyte altered the contents of SOC, TN, TP, AN and NN in non‐rhizosphere soil, which was consistent with other studies demonstrating that Epichloë endophyte changes soil properties due to litter decomposition (Franzluebbers et al, 1999; Khayamim et al, 2011; Zhou et al, 2014). However, this paper is the first research to evaluate the effect of litter containing Epichloë endophyte on chemical and biological properties in non‐rhizosphere soil.…”
Section: Discussionsupporting
confidence: 92%
“…Epichloë endophyte‐infected plants have higher SOC in the rhizosphere than endophyte‐free plants in a 15‐year trial (Franzluebbers et al, 1999). In the present study, we demonstrated that litter containing Epichloë endophyte altered the contents of SOC, TN, TP, AN and NN in non‐rhizosphere soil, which was consistent with other studies demonstrating that Epichloë endophyte changes soil properties due to litter decomposition (Franzluebbers et al, 1999; Khayamim et al, 2011; Zhou et al, 2014). However, this paper is the first research to evaluate the effect of litter containing Epichloë endophyte on chemical and biological properties in non‐rhizosphere soil.…”
Section: Discussionsupporting
confidence: 92%
“…The main mechanisms in the dissolution of silicates by SDB bacteria are exudation of excess proton and organic ligands (Barker et al 1998;Vandevivere et al 1994). Khayamim et al (2010) demonstrated that the vermiculization process can be promoted by proton-exchange process. Marie-Pierre et al (2009) demonstrated that biological activity can significantly influence the dissolution of Ca-bearing minerals such as labradorite and apatite and the dissolution of these minerals can occur under low Ca concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Epichloë endophyte infection can induce the differential expression of alkaloids and root metabolites in host plants, to alter the properties of rhizospheric soil (Handayani et al., 2011; Hecke et al., 2005). The effects of endophyte infection on the soil properties of host plants were highly variable, mainly dependent on host plant types and endophyte strain genotypes (Hayamim et al., 2010). Additionally, the effects Epichloë endophyte on soil chemical properties in the rhizospheric of host plants are closely related to the length of treatment cycle, treatment types, and environmental conditions, which supports our results (Franzluebbers & Stuedemann, 2002; Franzluebbers et al., 1999; Iqbal et al., 2012; Rojas et al., 2016).…”
Section: Discussionmentioning
confidence: 99%